Influence of commercially available follicle stimulating hormone on the in vitro maturation of bovine oocytes - Santos, Maria Valéria de Oliveira; Queiroz Neta, Luiza Bento de; Borges, Alana Azevedo; Pereira, Alexsandra Fernandes (Semina: Ciências Agrárias, 2017)
The work aimed (Experiment I) to compare commercial representations of porcine follicle stimulating hormone (FSH, Pluset® vs. Folltropin®) in concentration (10 ?g/mL) and time (24 h) standard (more used in protocols of in vitro maturation, IVM); (Experiment II) to evaluate the best incubation time (6 h vs. 16 h vs. 24 h) and, (Experiment III) analyze varying concentrations (1.0 ?g/mL vs. 2.5 ?g/mL vs. 10.0 ?g/mL) of representations of FSH on the IVM of bovine oocytes. Thus, oocytes were recovered and submitted to IVM under appropriate conditions. After the IVM, oocytes were evaluated for expansion of cumulus cells (CCs), presence of the first polar body (1PB) and metaphase plate (MII). All the data were analyzed by the Fisher exact test (P < 0.05). Initially, in Experiment I, no difference (P > 0.05) was observed in maturation rates of the oocytes incubated with FSH Pluset® or Folltropin®, assessed by expansion of CCs (97.6% vs. 94.3%), presence of 1PB (76.6% vs. 69.4%) and MII (70.0% vs. 68.6%). In Experiment II, when the incubation time with FSH was evaluated, both Pluset® as Folltropin® showed lower rate of expansion of CCs when they were present only in the first 6 h of IVM. As for presence of 1PB, differences were observed in relation to Pluset® while Folltropin® showed similar results in all incubation times. Regarding the MII, no difference was observed between the incubation times with FSH Pluset® and Folltropin®. In Experiment III, no difference was observed in the expansion of CCs, presence of 1PB and MII for concentrations evaluated FSH Pluset® and Folltropin®. Therefore, the FSH Pluset® and Folltropin® have the same efficiency in IVM of bovine oocytes. Regarding the incubation time, it is recommended to maintain FSH (Pluset® or Folltropin®) throughout the period of IVM, since there was no difference in the results of presence of MII. Furthermore, the concentration of 1.0 ?g/mL of FSH Pluset® and Folltropin® is as effective as 10 ?g/mL and can therefore be used for IVM of oocytes.